Variations in the content of astringent substances in different sorghum hybrids at different maturity stages - Rubiolo, O. J.; Reinaudi, N. B.; Domínguez, R. A.; Vaquero, J. (Facultad de Ciencias Agropecuarias, 1990)
Variation data of tannic acid equivalents in kernels of 38 grain sorghum hybrids at three different stages: solft dough, hard dough and ripening time are presented here. By means cluster annalysis four groups are differentiated. 1) With low tannin values at three stages. II) With high values at soft dough with a decreasing trend. III) Idem II but with higher values. IV) High values at soft doug, low at hard dough and highest values at ripening time.